2020
DOI: 10.1177/0194599820917619
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Frenotomy Techniques for the Treatment of Ankyloglossia in Children: A Systematic Review

Abstract: Objective To compare the effectiveness of conventional (CF), laser (LF), and Z-plasty (ZF) frenotomies for the treatment of ankyloglossia in the pediatric population. Data Sources A comprehensive search of PUBMED, EMBASE, and COCHRANE databases was performed. Review Methods Relevant articles were independently assessed by 2 reviewers according to the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines. Results Thirty-five articles assessing CF (27 articles), LF (4 articles), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 49 publications
0
23
0
3
Order By: Relevance
“…We found no strong evidence to support that ankyloglossia caused speech problems. Khan's article 7 in 2020, which included six studies, 4,5,17,22,23,33 among which one was excluded from our review due to the absence of speech‐related outcomes, 33 reviewed the divergence of language improvement effects among three different tongue‐tie division surgical techniques (conventional, laser, and Z‐plasty frenotomies). The results from this study pointed out the lack of unified standard measuring methods for postoperative speech changes and reported that Z‐plasty frenotomy had the benefit of preventing scar contracture.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We found no strong evidence to support that ankyloglossia caused speech problems. Khan's article 7 in 2020, which included six studies, 4,5,17,22,23,33 among which one was excluded from our review due to the absence of speech‐related outcomes, 33 reviewed the divergence of language improvement effects among three different tongue‐tie division surgical techniques (conventional, laser, and Z‐plasty frenotomies). The results from this study pointed out the lack of unified standard measuring methods for postoperative speech changes and reported that Z‐plasty frenotomy had the benefit of preventing scar contracture.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the indications, frenotomy is the primary surgical treatment option, which can be further classified into simple release (frenotomy, frenulotomy, or frenectomy) and suturing‐followed surgery (frenuloplasty) 7 . According to the surgical instruments, tongue‐tie division can be accomplished by conventional and laser surgical tools.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on studies, laser surgery technique has been shown to be superior to classical surgical intervention in terms of reduced discomfort while speaking and chewing, shorter procedure time, better bleeding control, less intra-and postoperative pain (3,24,25). The choice of laser technique eliminates the need for suture removal and is associated with increased acceptance among patients (26).…”
Section: Treatment Optionsmentioning
confidence: 99%
“…Warto również zauważyć, że pozytywny efekt na gojenie się rany pooperacyjnej miało wstrzyknięcie kwasu hialuronowego po zabiegu (23). Na podstawie przeprowadzonych badań wykazano przewagę techniki chirurgii laserowej w stosunku do klasycznej interwencji chirurgicznej w zakresie zmniejszonego dyskomfortu podczas mówienia i żucia, krótszego czasu zabiegu, lepszej kontroli krwawienia, mniejszego bólu śród-i pooperacyjnego (3,24,25). Wybór techniki laserowej eliminuje potrzebę usuwania szwów, a także wiąże się ze wzrostem akceptacji wśród pacjentów (26).…”
unclassified